Ambulatory Physical Activity in Swiss Army Recruits - Wyss, T.; Scheffler, J.; Mäder, U. (International Journal of Sports Medicine, 2012)
The aim of this study was to objectively assess and compare the type, duration and intensity of physical activity during the basic training provided by each of 5 selected Swiss Army occupational specialties. The first objective was to develop and validate a method to assess distance covered on foot. The second objective was to describe and compare physical activity levels among occupational specialties. In the first part of the study, 30 male volunteers completed 6 laps of 290 m at different gait velocities. Data from 15 volunteers were used to develop linear regression equations for the relationship between step frequency and gait velocity, and data from the other 15 volunteers were used to verify the accuracy of these equations. In the second part of the study, 250 volunteers from 5 military schools (each training school for a different occupational specialty) wore heart-rate, acceleration and step-count monitors during workdays of weeks 2, 4, 8 and 10 of their basic training. Sensor data were used to identify physically demanding activities, estimate energy expenditure (based on already published algorithms) and estimate distance covered on foot (based on the algorithm developed in the first part of this study). A branched model using 2 regression equations (gait velocity=0.705∙step frequency for walking speeds below 1 m/s and gait velocity=1.675∙step frequency – 1.464 for faster gait velocities) was shown to be accurate for estimating distance covered on foot. In the training schools investigated, average physical activity energy expenditure was 10.5±2.4 MJ per day, and trainees covered 12.9±3.3 km per day on foot. Recruits spent 61.0±23.3 min per day marching and 33.1±19.5 min per day performing physically demanding materials-handling activities. Average physical activity energy expenditure decreased significantly from week 2 to week 8. The measurement system utilised in the present study yielded data comparable to those of prior studies that applied alternative methods. Nevertheless, the new sensor-based, objective measurement system used provided more information on daily physical activity and demands than traditional, single measurement instruments. The average daily total energy expenditure values in all training schools investigated were within the range found for the armed forces of other nations and for professional athletes.
Keywords: energy expenditure; walking distance; body-wearable sensors; physical requirements; physical demands; military occupational specialties